METTL16 participates in haemoglobin H disease through m6A modification - Liao, Yuping; Zhang, Feng; Yang, Fang; Huang, Shijin; Su, Sha; Tan, Xuemei; Zhong, Linlin; Deng, Lingjie; Pang, Lihong (PloS one, 2024)
Haemoglobin H (HbH) disease is caused by a disorder of α-globin synthesis, and it results in a wide range of clinical symptoms. M6A methylation modification may be one of the mechanisms of heterogeneity. Therefore, this article explored the role of methyltransferase like 16 (METTL16) in HbH disease. The results of epigenetic transcriptome microarray were analysed and verified through bioinformatic methods and qRT-PCR, respectively. The overexpression or knock down of METTL16 in K562 cells was examined to determine its role in reactive oxygen species (ROS), cell cycle processes or iron overload. YTH domain family protein 3 (YTHDF3) was knocked down in K562 cells and K562 cells overexpressing METTL16 via siRNA to investigate its function. In addition, haemoglobin expression was detected through benzidine staining. qRT-PCR, WB, methylated RNA Immunoprecipitation (MeRIP) and (RNA Immunoprecipitation) RIP experiments were conducted to explore the mechanism of intermolecular interaction. METTL16, YTHDF3 and solute carrier family 5 member 3 (SLC5A3) mRNA and the methylation level of SLC5A3 mRNA were downregulated in HbH patients. Insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) mRNA expression was negatively correlated with HGB content among patients with HbH-CS disease. Overexpression of METTL16 increased ROS and intracellular iron contents in K562 cells, changed the K562 cell cycle, reduced hemin-induced haemoglobin synthesis, increased the expressions of SLC5A3 and HBG and increased SLC5A3 mRNA methylation levels. Knockdown of METTL16 reduced ROS and intracellular iron contents in K562 cells. Hemin treatment of K562 cells for more than 14 days reduced the protein expressions of METTL16 and SLC5A3 and SLC5A3 mRNA methylation levels. Knockdown of YTHDF3 rescued the intracellular iron content changes induced by the overexpression of METTL16. The RIP experiment revealed that SLC5A3 mRNA can be enriched by METTL16 antibody. METTL16 may affect the expression of SLC5A3 by changing its m6A modification level and regulating ROS synthesis, intracellular iron and cycle of red blood cells. Moreover, METTL16 possibly affects the expression of haemoglobin through IGF2BP3, which regulates the clinical phenotype of HbH disease.